Formal and Informal Communication Channels in Creating Corporate Brand Image and Preference - Ivana First; Marija Tomić (Tržište, 2011)
This study analyzes the effect that various communication channels have on corporate brand image creation among potential employees. Empirical data was collected by a survey conducted on a sample of 370 graduate students. The results revealed that more than ¾ of potential employees learn about the studied company through informal communication channels. Nevertheless, students of the faculties which organize formal company presentations are much better acquainted with such companies than the students of faculties where no formal presentations are held. Furthermore, within the scope of mono-channeled communication, there is no difference in the manner in which formal and informal channels influence brand knowledge and feelings. On the other hand, multi-channeled communication has a greater influence on both knowledge and feelings than mono-channeled communication. Finally, brand feelings are a stronger factor than brand knowledge in determining brand preference but knowledge also determines feelings. These results have several practical implications. Although informal communication has a wider range of resonance, formal communication is more important and should not be neglected by practitioners. Formal communication is not only able to create positive brand image equally well but it also acts as a trigger for informal communication. Practitioners facing limited resources are further advised to give priority to the communication that creates brand feelings rather than brand knowledge.